EVALUATION OF THE RESULTS OF MICROSURGICAL VARICOCELECTOMY AT 19-8 HOSPITAL, MINISTRY OF PUBLIC SECURITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the effectiveness and safety of microsurgical varicocelectomy at 19-8 Hospital, Ministry of Public Security.Subjects and methods: A descriptive retrospective case-series study was conducted on 165 patients who underwent microsurgical varicocelectomy at the Department of Urology, 19-8 Hospital from December 2022 to December 2025. Clinical characteristics, Doppler ultrasound findings, semen parameters, and complications were assessed before surgery and at 1 and 3 months postoperatively.Results: The mean age was 27.6 ± 6.8 years. Scrotal pain was present in 86.1% of patients, and palpable varicocele was found in 65.5%. The success rate was 96.4%, and the failure rate was 3.6%. The mean spermatic vein diameter decreased significantly from 3.12 ± 0.58 mm preoperatively to 1.82 ± 0.49 mm at 3 months postoperatively (p < 0.05). Semen parameters improved significantly, with sperm concentration increasing from 28.5 ± 24.7 to 45.6 ± 31.2 million/ml, total sperm count from 102.4 ± 118.6 to 176.3 ± 150.5 million, and progressive motility from 34.2 ± 12.1% to 41.8 ± 13.4% (p < 0.05). Complications were minimal and mostly mild.Conclusion: Microsurgical varicocelectomy is a safe and effective method for the treatment of varicocele.
Keywords: Varicocele, microsurgery.